Assessing Macro-Financial Risks of Household Debt in China - Han, Fei (IMF Working Papers; Working Paper ;, 2019)
High household indebtedness could constrain future consumption growth and increase financial stability risks. This paper uses household survey data to analyze both macroeconomic and finanical stability risks from the rapidly rising household debt in China. We find that rising household indebtedness could boost consumption in the short term, while reducing it in the medium-to-long term. By stress testing households' debt repayment capacity, we find that low-income households are most vulnerable to adverse income shocks which could lead to signficant defaults. Containing these risks would call for a strengthening of systemic risk assessment and macroprudential policies of the household sector. Other policies include improving the credit registry system and establishing a well-functioning personal insolvency framework.